PENINGKATAN HASIL BELAJAR IPA SISWA KELAS V SD INPRES 12/79 CELLU 1 MELALUI PENERAPAN MODEL PEMBELAJARAN QUANTUM BERBASIS HUMANISTIS - Sudarto Sudarto; Achmad Shabir; M. Reski Ramadhan (Bajang Institute, 2024)
This research was motivated by the application of a humanistic-based Quantum learning model to improve the students' science learning outcomes in the 5th Grade at SD Inpres 12/79 Cellu 1 Bone Regency. The aim of this research is to find out whether the implementation of humanistic-based Quantum learning model can or can not improve the science learning outcomes of the 5th Grade students at SD Inpres 12/79 Cellu 1, East Tanete Riattang District, Bone Regency. The subjects in this research were all of the fifth grade students at SD Inpres 12/79 Cellu 1, East Tanete Riattang District, Bone Regency in totaling 15 students. The data collection technique used was the test technique. The data analysis technique used is a quantitative descriptive. Research results: the number of the students who completed cycle I was of 9 people (60%) and in cycle II was of 12 people (80). Conclusion: the application of a humanistic-based Quantum learning model can improve the science learning outcomes of the fifth grade students at SD Inpres 12/79 Cellu 1, East Tanete Riattang District, Bone Regency.